The impact of experimental forest fire on collembolan communities - Izabella Olejniczak; Anna Prędecka; Stefan Russel (Studia Ecologiae et Bioethicae)
Our study was carried out in fresh pine mixed forest, Biala Forest, near Warsaw (52°59’ N, 21°46’ E and 52°79’ N, 21°89’ E, Eastern Poland). Three experimental plots, 1m2 size, were chosen at random and burnt in June. The material was collected: just after the experimental fire (in June ), 30, 60, and 90 days after fire (respectively: in July, August, and September). On every sampling occasion 10 soil samples of an area of 10cm2 and a depth of 5 cm were taken in each sampling plots: burnt plots, in the border of burnt plots, and in surroundings of burnt plots.